1997
DOI: 10.1590/s0100-879x1997001200015
|View full text |Cite
|
Sign up to set email alerts
|

The rate of force generation by the myocardium is not influenced by afterload

Abstract: The influence of afterload on the rate of force generation by the myocardium was investigated using two types of preparations: the in situ dog heart (dP/dt) and isolated papillary muscle of rats (dT/dt). Thirteen anesthetized, mechanically ventilated and thoracotomized dogs were submitted to pharmacological autonomic blockade (3.0 mg/ kg oxprenolol plus 0.5 mg/kg atropine). A reservoir connected to the left atrium permitted the control of left ventricular end-diastolic pressure (LVEDP). A mechanical constricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The authors who assessed the relationship between these 2 variables considered that, during oscillations of BP, the values of dP/dt may be modified as a result of variations in the afterload or in the coronary perfusion. Studies conducted in our laboratory [29][30][31] , whose methods were similar to those used in the present study, showed that, in the experimental conditions that we used, the sudden increase in the aortic pressure did not affect the values of dP/dtmax.…”
Section: Discussionmentioning
confidence: 61%
“…The authors who assessed the relationship between these 2 variables considered that, during oscillations of BP, the values of dP/dt may be modified as a result of variations in the afterload or in the coronary perfusion. Studies conducted in our laboratory [29][30][31] , whose methods were similar to those used in the present study, showed that, in the experimental conditions that we used, the sudden increase in the aortic pressure did not affect the values of dP/dtmax.…”
Section: Discussionmentioning
confidence: 61%